Functional Involvement of Carbonic Anhydrase in the Lysosomal Response to Cadmium Exposure in Mytilus galloprovincialis Digestive Gland - Caricato, Roberto; Giordano, M. Elena; Schettino, Trifone; Lionetto, M. Giulia (Frontiers in Physiology, 2018)
Carbonic anhydrase (CA) is a ubiquitous metalloenzyme, whose functions in animals span from respiration to pH homeostasis, electrolyte transport, calcification, and biosynthetic reactions. CA is sensitive to trace metals in a number of species. In mussels, a previous study demonstrated CA activity and protein expression to be enhanced in digestive gland by cadmium exposure. The aim of the present work was to investigate the functional meaning, if any, of this response. To this end the study addressed the possible involvement of CA in the lysosomal system response of digestive gland cells to metal exposure. The in vivo exposure to acetazolamide, specific CA inhibitor, significantly inhibited the acidification of the lysosomal compartment in the digestive gland cells charged with the acidotropic probe LysoSensor Green D-189, demonstrating in vivo the physiological contribution of CA to the acidification of the lysosomes. Under CdCl2 exposure, CA activity significantly increased in parallel to the increase of the fluorescence of LysoSensor Green charged cells, which is in turn indicative of proliferation and/or increase in size of lysosomes. Acetazolamide exposure was able to completely inhibit the cadmium induced Lysosensor fluorescence increase in digestive gland cells. In conclusion, our results demonstrated the functional role of CA in the lysosomal acidification of Mytilus galloprovincialis digestive gland and its involvement in the lysosomal activation following cadmium exposure. CA induction could physiologically respond to a prolonged increased requirement of H+ for supporting lysosomal acidification during lysosomal activation.